Identification of immunomodulators associated with atrial fibrillation reporting to better understand AF immunologic mechanisms: a Vigibase retrospective disproportionality analysis and a literature review - Font, Jonaz; Dolladille, Charles; Divoux, Jordane; Chrétien, Basile; Boysson, Hubert; Legallois, Damien; Ollitrault, Pierre; Champ-Rigot, L.; Ferchaud, Virginie; Pellissier, Arnaud; Milliez, Paul; Alexandre, Joachim (BMJ Open, 2026)
OBJECTIVES: Growing evidence exists about the pivotal role of immune mechanisms in the physiopathology of atrial fibrillation (AF). Drugs that modulate the immune system (immunomodulators) may contribute to the development of AF. We aimed to identify immunomodulators that are associated with AF to better define their safety profile, and elucidating their mechanisms of action could yield novel insights into AF's immune physiopathology. DESIGN: A descriptive and disproportionality analysis of claims data. SETTINGS: World pharmacovigilance database VigiBase until 1 March 2025. PRIMARY AND SECONDARY OUCTOMES: First, we ascertained the association of immunomodulators with AF over-reporting with a disproportionality analysis evaluating the multivariable-adjusted reporting odds ratio (aROR) for AF reporting performed for 141 immunomodulators in VigiBase. Then, a literature review was done to explore the underlying mechanisms of AF through immunomodulator mechanisms. RESULTS: A total of 6 148 556 reports encompassing at least one of the 141 immunomodulators were identified in Vigibase. Our primary analysis revealed 20 immunomodulators associated with AF over-reporting. The three immunomodulators with the greatest signal were: recombinant interleukin-11 with an aROR=20.91 (99.96% CI 12.08 to 36.17), efgartigimod alfa with an aROR=6.75 (99.96% CI 3.96 to 11.52) and recombinant interleukin-2 with an aROR=6.15 (99.96% CI 3.62 to 10.45). A derivative literature review posited a hypothetical immune 'vicious circle' promoting AF, involving T helper cells, macrophages and natural killer cells which could lead to electrophysiologic and histologic atrial remodelling. CONCLUSIONS: Twenty Food and Drug Administration (FDA)-labelled immunomodulators are associated with AF overreporting in Vigibase with a substantial signal on recombinant IL-11. These data contribute substantively to the prevailing understanding of the safety profile of these immunomodulators. Moreover, these findings support a multidirectional interaction between the immune system and AF development and might lead to considering future therapeutic targets. TRIAL REGISTRATION NUMBER: NCT06095791.